Hearts and minds: Children's experiences of Disney world - Pettigrew, Simone (Routledge, 2011)
Children’s experiences of theme parks were investigated using a broad range of data collection methods. The aim of the study was to assess the extent to which overall perceived enjoyment of the theme park experience is related to incidentspecific evaluations, periodic mood ratings, and levels of physiological excitement. The results show that for the two children participating in this study, Magic Kingdom did not provide superior experiences in terms of heart rate, mood, rides, and shows, despite the children reporting that they enjoyed this park more than the other parks visited. Expectations may have disproportionately influenced the children’s evaluations of their Disney World experience due to thestrength of the Disney brand among members of this age group. It thus seems that the idea of Disney World may be assimilated more intensely than the experienced reality.